Performance Measurement Design Based on Balanced Scorecard and Analytical Hierarchy Process (AHP): A Case in Indonesian Packaging Company - darno DARNO; khadijah binti md; ARIFIN; resista; VIKALIANA; hariyati; HARYATI; anieq; FARDAH (Communications of International Proceedings, 2022)
Balanced Scorecard is a performance management tool that can help organizations translate vision and strategy into action based on financial and non-financial indicators. There are four aspects measured in the Balanced Scorecard (BSC) namely financial perspective, customer perspective, internal business process perspective, and growth and learning perspective. This research aims to find out how PT. PQRS, a food and beverage packaging company using the concept of Balanced Scorecard. Analytical by Hierarchy Process (AHP), identification of strategic target and management needs, found 16 KPIs (Key Performance Indicators), consisting of 5 KPIs on a financial perspective, 3 KPIs on a customer perspective, 4 KPIs on an internal business process perspective, and 4 KPIs on a learning and growth perspective. Overall, company performance achievement index is a good category. The results of the measurement of the company's financial performance obtained a fariative result. The results of measuring the company's non-financial performance at the rate of increase in the number of customers have pretty good score criteria. In the measurement of internal business perspective according to respondents, the criteria are good and in the measurement of learning and growth perspective has good score criteria.
Keywords: Balanced Scorecard; Key Performance Indicator; Analytical Hierarchy Process